Games and Health Education for Diabetes Control: A Systematic Review with Meta-Analysis - Martos-Cabrera, María Begoña (Healthcare (Basel), 2020)
Finding methods to improve people’s diabetes control and management is important to prevent its complications and maintain the quality of life. The aim of this review was to assess the effect of games on the blood glucose level (glycated hemoglobin (HbA1c)). A systematic review and meta-analysis were made. Pubmed, Scopus, and CINAHL databases were consulted in July of 2020. Ten studies were selected as a final sample, most of them being clinical trials using games to improve diabetes control. Half of the studies had samples between 8 and 14.9 years old and the other half between 57 and 65 years old. The studies informed about using applications/games for mobile phones, game consoles, and board games for diabetes education and management. The meta-analysis was performed with 4 studies showing a mean difference of 0.12 (CI 95% 0.57, 0.33) of HbA1c in favor of the intervention group with p > 0.05. Games are positive for diabetes health education and promoting healthier lifestyle, but their impact on HbA1c is low.